SISTEM PEMBUKTIAN PEMALSUAN DOKUMEN DALAM TINDAK PIDANA PEMILU DI INDONESIA - M. Khaerul; Amir Ilyas; Audyna Mayasari Muin (JURNAL ILMIAH LIVING LAW, 2022)
In the proof system for falsifying documents in election crimes, of course, it requires a good process in terms of applying sanctions for violators if they are proven to have committed an election crime, seen from material and formal legal facts and supported by evidence submitted starting from the investigation process, investigation to the court so that the trial process can determine whether the defendant is guilty or not, based on the evidence presented. As well as the application of sanctions regulated in the law, both specifically and generally. The proof system for falsification of documents in election crimes in Indonesia refers to Law Number 8 of 1981 concerning the Criminal Procedure Code (KUHP), and is also based on evidence presented at trial. 2) The legal implications of the document falsification system in electoral crimes in Indonesia in terms of formal and material legal regulations in Law Number 7 of 2017 concerning General Elections, and the administration of elections as well as law enforcement officers in election crimes